AUTHIGENIC 10BE/9BE SIGNATURE OF THE LASCHAMP EXCURSION: A TOOL FOR GLOBAL SYNCHRONISATION OF PALEOCLIMATIC ARCHIVES - Leduc G.; Thouveny N.; Bourlès D.L.; Blanchet C.L.; Carcaillet J.T. (My University, 2006)
Authigenic 10 Be and 9 Be isotope concentrations have been measured in marine sediments deposited between 10 and 60 ka BP in the western equatorial Pacific and their ratio compared to the geomagnetic relative paleointensity (RPI) record obtained from the same core [C.L. Blanchet, N. Thouveny, T. de Garidel-Thoron, New evidences of geomagnetic moment lows between 30 and 45 ka BP from a sedimentary sequence of the west equatorial Pacific, Quat. Sci Rev. (in press)]. Over the studied time interval, dated by radiocarbon and oxygen isotope stratigraphy, three periods of reduced RPI occurring at ∼ 32, 37 and 45 ka, according to the constructed age model, are concomitant with three significant increases in atmospheric 10 Be production. Since the most pro-minent 10 Be/ 9 Be peak necessarily results from the weakest geomagnetic moment event, i.e. that associated with the Laschamp excursion, we assign to this cosmogenic nuclide event the age of the Laschamp excursion (i.e. 40.4 ± 2.0 ka BP) [H. Guillou, B.S. Singer, C. Laj, C. Kissel, S. Scaillet, B.R. Jicha, On the age of the Laschamp geomagnetic excursion, Earth Planet. Sci. Lett. 227 (2004) 331–343]. Cosmogenic nuclide production peaks provide critical complementary evidence for the identification of geomagnetic dipole lows linked to excursions and constitute accurate markers for global intercorrelation of paleoclimatic archives.
Keywords: cosmogenic nuclides; geomagnetic field intensity; Laschamp excursion; correlation of geological record